The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1242/jcs.133280
|View full text |Cite
|
Sign up to set email alerts
|

Integrins Promote Cytokinesis through the RSK Signaling Axis

Abstract: Cytokinesis is the final stage in cell division. Although integrins can regulate cytokinesis, the mechanisms involved are not fully understood. In this study, we demonstrate that integrin-regulated ERK (extracellular signal-related kinase) and RSK (p90 ribosomal S6 kinase) signaling promotes successful cytokinesis. Inhibiting the activation of ERK and RSK in CHO cells by a mutation in the integrin b1 cytoplasmic tail or with pharmacological inhibitors results in the accumulation of cells with midbodies and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…They used BJ fibroblast cells and, in this study, we used RAW 264.7 macrophages. The difference may be a result of the cell type-specific response to FAK inhibitors or cell type specificity in the regulation of cytokinesis that has been suggested in previous studies [11,22]. There are two possible reasons for the difference.…”
Section: Discussionmentioning
confidence: 85%
“…They used BJ fibroblast cells and, in this study, we used RAW 264.7 macrophages. The difference may be a result of the cell type-specific response to FAK inhibitors or cell type specificity in the regulation of cytokinesis that has been suggested in previous studies [11,22]. There are two possible reasons for the difference.…”
Section: Discussionmentioning
confidence: 85%
“…Although our previous studies demonstrated that both RSK1 and RSK2 regulated cytokinesis in MCF10A cells (14), these studies did not determine whether both isoforms functioned downstream of integrins or whether they regulated cytokinesis by similar mechanisms. To begin, we confirmed that both RSK1 and RSK2 regulated cytokinesis in SIMS cells.…”
Section: Rsk2 Functions Downstream Of α6 Integrinsmentioning
confidence: 77%
“…However, since integrin signaling can be strongly influenced by substrate compliance (23), and our previous studies demonstrated that cytokinesis is regulated by matrix compliance in a cell typedependent manner (24), it is important to demonstrate that pathways that regulate cytokinesis in cell culture similarly regulate cytokinesis in a more physiological complex context. Since we previously demonstrated that α6 integrins promote successful cytokinesis in embryonic salivary glands in ex vivo organ culture (14), we again used this model to test whether RSK2 regulates cytokinesis and MKLP1 expression in this context. To this end, submandibular salivary glands were isolated from mouse embryos at embryonic day 12.5 -13 (E12.5-E13) and treated for 3 days with either nontargeting or RSK2-targeting siRNA (Fig.…”
Section: Rsk2 Regulates the Expression Of Mklp1 In The Embryonic Salimentioning
confidence: 99%
See 2 more Smart Citations